The Effect of Educational Intervention based on BASNEF Model on Decreasing the Cesarean Section Rate among Pregnant Women in Khomain County - Zohreh Arefi; Davod Hekamatpou; Mohammad ali Orouji; Zahra Shaahmadi; Giti Khushemehri; Faramarz Shaahmadi (Tehran University of Medical Sciences, 2015)
Objective:Over the past two decades, the incidence of cesarean section in most countries has increased. Cesarean section increases the risk of death and complications in the mother and fetus. Educational interventions based on behavior change models can play an important role in reduce the rate of cesarean section. The aim of our study is investigation the effect of educational intervention based on BASNEF Model on decreasing of cesarean section rate among pregnant women in Khomain County, from June to November 2013. Materials and methods:In this interventional study, 140 nulliparous women who were in their last trimester of pregnancy were randomly allocated to case and control groups. Data gathering instrument was a questionnaire based on BASNEF framework. Data were analyzed by SPSS14 software. Results:The scores of knowledge, attitudes, subjective norms, and enabling factors in the intervention group than the control group showed a significant difference (p <0.001). After the study, it was found that 18 women (25.7%) in case group and 42 women (60%) in the control group underwent cesarean section. By Chi-square test showed that the difference in the type of delivery between the two groups was statistically significant (p<0.001). Conclusion:Design and implement curriculum based on BASNEF can be effective in reducing elective cesarean section.